Religiusitas Dengan Regulasi Emosi Pada Ibu Single Parent - Erma Nursanti; Nugraheni Gadis; Lilik Hariyanto (Universitas Darul Ulum, 2021)
The focus of this research is to see if there is a correlation between religiosity and emotional control in parenting of single mothers. There is a link between religiosity and emotion control, according to the hypothesis. The respondents in this study were 40 single mothers from Jombang. Purposive random sampling was utilized in this study as a sample technique. This study used a religious scale and an emotion regulation scale to collect data. Spearman's rho was utilized to analyze the data. Using Sperman's rho analysis, it was determined that r rho = 0.798 and sig. = 0.00 (p 0.01). This reveals that in single parent mothers, there is a significant positive relationship between religion and emotional regulation, with the higher the religiosity, the higher the emotional control. On the other hand, the lesser one's religiosity, the poorer one's emotional regulation. As a result, the study's hypothesis is accepted. Key words : Religiosity, Emotion Regulation, and Single mother Parenting